A textual analysis of Pseudo-Ezekiel (4Q385 & 4Q386) in order to determine its dating in the light of ancient scribal practices - Schader, Jo-Mari (University of Pretoria, 2019)
Dissertation (MA)--University of Pretoria, 2019.